Morning Cortisol Patterns in Mental Health: (Depression, Anxiety, and Stress) - Ridwan M. Alomri (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Cortisol is well known as a hormone that is released as a repones of the hypothalamic-pituitary-adrenal axis, which was found to be associated with depression, anxiety, and stress. However, the role of morning cortisol patterns, particularly the cortisol awakening response, remains unclear. This study aimed to demonstrate the association between morning cortisol levels and mental health conditions. 88 participants have been included to undergo a blood test to measure the morning blood cortisol and depression, anxiety and stress levels were measured using Depression, Anxiety and Stress Scale-21. The findings indicated that individuals with depressive symptoms not anxiety or stress showed elevated morning cortisol. This study concludes that morning blood cortisol could be used as an early detector for depression.